Corporate Taxation of Heterogeneous Firms and the Welfare Effects of Labour Unions. (15th January 2016) - Schneider, Andrea
Abstract: This paper examines the welfare effects of powerful labour unions when the government levies a uniform tax rate – as is currently the case in most OECD countries – and firms are heterogeneous with respect to productivity. I show that an increase in the bargaining power of labour unions can decrease the welfare loss generated by restriction of the tax policy and provide conditions under which powerful labour unions decrease the likelihood that firms will move abroad. I also reproduce the well‐known effect whereby powerful labour unions decrease corporate tax rates if firms are mobile.